Power Relationships and Transitivity Choices in Graham Greene’s Dream of a Strange Land - Khan, Saadia; Rahman, Rubina (The Journal of Humanities & Social Sciences, 2023)
Stylistic analysis of a text uses many tools from linguistic research. Halliday’s model of transitivity choices offers one such method of textual investigation. Transitivity choices construct the reality of the text world and its characters. Burton (1996) takes a feminist stance and traces power relationship in Plath’s The Bell Jar where she establishes female character as a victim in power dynamics. This paper is an attempt to establish the pattern of power relationship in a male oriented domain in Greene’s short story Dream of a Strange Land. The paper concludes that power relationships are not necessarily gender bound. They are found between humans as a part of their existence.